The penelopiad: a reconstrução do mito por margaret atwood - Leite, Maria do Rosário Silva (2010)
The present work analyses the novel The Penelopiad: The Myth of Penelope and Odysseus (2005), by the Canadian author Margaret Atwood, translated into Portuguese as A Odisséia de Penélope (2005), a narrative characterized as a recreation of the homeric myth. This novel offers its reader an opportunity of coming back to Greece, now having Penelope as a protagonist and narrator, opening the possibilities of representing this figure of classical myhtology beyond Homer s representations. According to Homer s narrative, in tune with patriarchal understanding of gender relations, women, specially Greek women, should become mothers and remain inside the gineceu, what his Penelope did. However, in the reconstruction and rereading of this epic text presented by Atwood, Penelope invites us to look through the brumes of the past in order to listen to possibly different arrangements about the story of her life. It is in this context that our work intends to present and discuss Atwood s Penelope, recognizing other possibilities of retelling this classic text, deconstructing Homer s view at different points and aspects. Thus, by examining the brackets, the intersticial spaces of the homeric narrative, Atwood reconstructs the character and the myth, enabling her Penelope to speak about everything that was silenced in the homeric text, revealing her view, opinion and explanation about those events.